2021
DOI: 10.1186/s13643-021-01781-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the effectiveness of technology-enabled dementia education for health and social care practitioners: a systematic review

Abstract: Background Dementia prevalence is increasing globally and yet evidence suggest that gaps exist in dementia-specific knowledge among health and social care practitioners. Technological modes of educational delivery may be as effective as traditional education and can provide practitioners with increased accessibility to dementia training. Benefits of digitally based dementia education have been established including pedagogical strategies that influence dementia knowledge and care attitudes. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 68 publications
(375 reference statements)
0
13
0
Order By: Relevance
“…Major advances in technology should also be leveraged to optimize the time and effectiveness of the dementia care workforce. As one example, e‐learning programs can greatly increase access to dementia care training, although evidence suggests that the effectiveness of such programs relies on the relevance of the content and the inclusion of interactive learning strategies 710 …”
Section: Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Major advances in technology should also be leveraged to optimize the time and effectiveness of the dementia care workforce. As one example, e‐learning programs can greatly increase access to dementia care training, although evidence suggests that the effectiveness of such programs relies on the relevance of the content and the inclusion of interactive learning strategies 710 …”
Section: Workforcementioning
confidence: 99%
“…As one example, e-learning programs can greatly increase access to dementia care training, although evidence suggests that the effectiveness of such programs relies on the relevance of the content and the inclusion of interactive learning strategies. 710 Technology can also help improve access to care for people living with dementia, especially for those in rural areas and those with mobility challenges. 711 A randomized clinical trial of more than 1,500 individuals across urban and rural areas in three states who participated in a telephone-and internet-based dementia care delivery system found that the system resulted in better quality of life, reduced emergency department visits, and decreased caregiver depression and burden.…”
Section: Leverage Technology To Augment Dementia Care Deliverymentioning
confidence: 99%
“…Evidence of attitude changes after technology-based training was not very convincing. However, improved knowledge can also influence practitioner attitudes [38].…”
Section: Discussionmentioning
confidence: 99%
“…The application of different AI-based methods and digitalization plans have been considered for the automation of work processes and upholding of social distancing [2,30,32,40,48,106,107]. It will be necessary to focus on the application of AI methods for career planning and consulting with students and fostering their decisionmaking.…”
Section: Innovative Methods Of Mentoring and Planningmentioning
confidence: 99%
“…The departments can establish different short-term skillbased programs and long-term educational courses in novel fields such as digital psychology, motivational courses for remote employees, and digital management, to name a few [1,2,11,20,22,40,56,104,105]. In particular, in some fields such as medical education new competencies will be expected from the graduates [30,32,48,106,107].…”
Section: Assessment Will Be the Tool Of Value Delivery And Innovationmentioning
confidence: 99%